Good connections: cultural dynamics for social inclusion = Dobre połączenia: dynamika kulturalna na rzecz inkluzji społecznej - Capelo, Regina; Varela, Miguel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Structural changes and social stratification in a rapidly changing world produce psychosocial and socio-cultural consequences that are expressed in mechanisms of discrimination and social exclusion and require the creation of mechanisms that motivate and reinforce culture as a strategy of social inclusion. This study describes the cultural dynamics for social inclusion developed in a vulnerable socio-economic context.
Keywords: podatność społeczna; wykluczenie społeczne; integracja społeczna; kultura; znajomości; social vulnerability; social exclusion; social inclusion; culture; connections